Answer:
<h2>2</h2>
Step-by-step explanation:
Given g(x)=5x-4 and g(x)=f^{-1}(x)-3
Substituting g(x) = 5x-4 into the second equation we have;
5x-4 = f^{-1}(x)-3
f^{-1}(x) = 5x-4+3
f^{-1}(x) = 5x-1
To get f(x), let us first make y to be equal f^{-1}(x)
y = 5x-1
expressing x in terms of y to get f(x), we have;
5x = y+1
x = y/5+1/5
replacing y with x, we will have;
y = x/5 + 1/5
F(x) = x/5 + 1/5
Comparing x/5 + 1/5 with ax+b, a = 1/5 and b = 1/5
5a + 5b = 5(1/5)+ 5(1/5)
5a+5b = 1+1
5a+5b = 2
Answer:
<h2>2 and three-fourths </h2>
Step-by-step explanation:
Given the expression , the equivalent expression can be gotten as shown;
2 and three-fourth therefore gives the required expression
2x / y = 16
2x because she made twice the shots with free throws then two point shots
(x+4)(x+4+1) = (x+1)(x+1+11)
(x+4)(x+5) = (x+1)(x+12)
x^2 + 4x+5x+20=x^2+x+12x+12
9x + 20 = 13x + 12
13x-9x = 20-12
4x = 8
x = 2